2021
DOI: 10.1007/s13304-021-01105-4
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa plication reinforced colorectal anastomosis and trans-anal vacuum drainage: a pilot study with preliminary results

Abstract: Dehiscence of colorectal anastomosis is a serious complication that is associated with increased mortality, impaired functional and oncological outcomes. The hypothesis was that anastomosis reinforcement and vacuum trans-anal drainage could eliminate some risk factors, such as mechanically stapled anastomosis instability and local infection. Patients with rectal cancer within 10 cm of the anal verge and low anterior resection with double-stapled technique were included consecutively. A stapler anastomosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Recently, it has been hypothesized that AL results from infectious complications caused by local enteric bacteria and that healing at the anastomosis is impaired by a local increase in collagenase activity [6], and Freko A et al reported that anastomotic healing disorders and "restlessness" observed in their analysis of photographic documentation of endoscopic ndings of anastomosis in rectal cancer surgery are associated with local ischemia and local infection, and they reported that the anastomotic healing disorders and restlessness in the anastomotic site are associated with local ischemia and local infection in a study of double-stapled anterior rectal cancer after lower anterior resection of the rectum [1]. The authors reported that the combination of double-staple reinforcement with a unique circular mucosal suture and povidone-iodine-impregnated vacuum sponge drainage resulted in a low rate of early suture failure in patients undergoing reconstruction using the double-stapled technique after low anterior resection of rectal cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been hypothesized that AL results from infectious complications caused by local enteric bacteria and that healing at the anastomosis is impaired by a local increase in collagenase activity [6], and Freko A et al reported that anastomotic healing disorders and "restlessness" observed in their analysis of photographic documentation of endoscopic ndings of anastomosis in rectal cancer surgery are associated with local ischemia and local infection, and they reported that the anastomotic healing disorders and restlessness in the anastomotic site are associated with local ischemia and local infection in a study of double-stapled anterior rectal cancer after lower anterior resection of the rectum [1]. The authors reported that the combination of double-staple reinforcement with a unique circular mucosal suture and povidone-iodine-impregnated vacuum sponge drainage resulted in a low rate of early suture failure in patients undergoing reconstruction using the double-stapled technique after low anterior resection of rectal cancer [7].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic trans-anorectal closure negative-pressure drainage technology uses flexible endoscopy to check the anastomosis and guide placement of suction sponges. 27 However, because of difficulty in the operation of the flexible mirror as well as poor directionality, intestinal contents easily contaminate the mirror surface, causing poor visualization. In addition, during colonoscopy, gas needs to be injected to expand the bowel, and the pressure is not easy to control.…”
Section: Discussionmentioning
confidence: 99%